Chemistry and Hygiene of Food Additives - Laganà, Pasqualina; Avventuroso, Emanuela; Romano, Giovanni; Gioffré, Maria Eufemia; Patanè, Paolo; Parisi, Salvatore; Moscato, Umberto; Delia, Santi (Springer International Publishing : Imprint: Springer, 2017)
This brief addresses important aspects of food additives. Through four chapters, the authors describe the chemistry of food additives, the regulatory classification of additives on a large-scale, the risks involved in using chemicals for food preparation - including implications this has on food hygiene, and case-study examples taken from the dairy industry. More specifically, chapter one provides a list of the technological purposes of food additives defined for European use; chapter two explains the 'General Standards for Food Additives' (Codex Alimentarius Commission) which is a harmonised, workable and indisputable international standard; chapter three describes the use of selected food additives in the dairy sector, particularly with relation to the production of yoghurt products; and chapter four addresses the impact of additives on human health. This brief is of interest to researchers working in the area of food production and international regulation, both in academia and industry.
Keywords: Chemistry.; Food -- Biotechnology.; Public health.; Agriculture.; International law.; elektronické knihy; electronic books